2016
DOI: 10.1039/c6py01421f
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular engineering polyesters: endgroup functionalization of glycol modified PET with ureidopyrimidinone

Abstract: We report the first supramolecular engineering polymer with melt viscosity suitable for non-degradative processing plus enhanced thermal and mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The progress of self‐healing was monitored at room temperature for approximately 1 h, whereupon no change was observed. The resins were heated to 80 °C in order to induce disassembly of UPy/UPy associations and observed at room temperature after 15 and 45 min. No visible changes were observed in the notch of the control resin B .…”
Section: Resultsmentioning
confidence: 99%
“…The progress of self‐healing was monitored at room temperature for approximately 1 h, whereupon no change was observed. The resins were heated to 80 °C in order to induce disassembly of UPy/UPy associations and observed at room temperature after 15 and 45 min. No visible changes were observed in the notch of the control resin B .…”
Section: Resultsmentioning
confidence: 99%
“…96,34 Therefore, a plethora of studies reported the contribution of UPy stacking on polymer dynamics as an inevitable part of this sticker. 97,98 This is indeed a big disadvantage when comparing with theories, although in some studies this effect has not been truly addressed. 99,100 For instance, in one study by Binder et al on PnBA end-capped with THY and/or DAT the absence of a plateau in the frequency sweeps was related to the absence of phase separation.…”
Section: Sticker Positionmentioning
confidence: 99%
“…Moreover, it was proposed that an additional stacking of the UPy groups is supported by hydrogen bonding of the urethane/urea groups next to the UPy moieties ( Van Beek et al, 2007 ; Bobade et al, 2014 ). An important additional contribution to the improved printability of such supramolecular “chain-extended” polymers is induced by avoiding phase segregation effects, as the UPy groups present in linear polymers ( Kan et al, 2019 ; Houston et al, 2016 ) can induce phase separation, in turn changing the relaxation behavior, then behaving more like shorter chains rather than long segregated systems ( Boothroyd et al, 2019 ; Golkaram et al, 2019 ). A third principle important in many supramolecular polymers is the formation of transient networks, formed by hydrogen bonds inside a thermoplastic polymer, which leads to supramolecular transient crosslinking between the chains ( Figure 3C ), in turn increasing melt viscosity and elasticity, able to facilitate 3D printing of such polymers ( Reppel et al, 2013 ; Döhler et al, 2020 ).…”
Section: Rheology Of Supramolecular Materialsmentioning
confidence: 99%